Examining the Influence of Prison on the Mental Conditions of Incarcerated Inmates - VIMBI PETRUS MAHLANGU (Social Sciences and Education Research Review, 2025)
This conceptual paper explores the influence of prison environments on the mental conditions of incarcerated inmates. The primary objective is to synthesize existing knowledge and interpretations from various scholarly sources to facilitate a more profound understanding of how incarceration impacts inmate psychological well-being. Data collection involved a systematic review of books and peer-reviewed articles published between 2021 and 2025, focusing specifically on the lived experiences of incarcerated individuals and the institutional factors affecting their mental health. The analysis was conducted using an interpretive paradigm, allowing for a nuanced and context-sensitive interpretation of the literature. Findings reveal that institutional neglect—particularly the absence of adequate educational and rehabilitative infrastructure—reflects a broader disregard for the intellectual and emotional development of inmates. The prison environment, characterized by isolation, limited autonomy, exposure to violence, and inadequate mental health services, contributes to the emergence and worsening of psychological symptoms. Notably, many individuals develop post-incarceration syndrome, exhibiting symptoms such as social disorientation, emotional numbing, difficulty in maintaining relationships, persistent anxiety, and hypervigilance. These conditions often persist long after release, severely hindering reintegration into society. The study underscores the urgent need for trauma-informed rehabilitative prison practices that prioritize the psychological well-being and social reintegration of inmates.